(untitled) (Innovative professional education, 2025)
The use of creative learning technologies in the training of future skilled workers is implemented within the framework of systemic, competency-based, activity-based, and personality-oriented approaches and is characterized by the presence of goals, patterns, general didactic and professional principles, components of the development of creativity of future skilled workers, methods and technologies, and forms of learning